The American racial divide in fear of the police - Pickett, Justin T. (Criminology, 2022)
The mission of policing is “to protect and serve,” but recent events suggest that many Americans, and especially Black Americans, do not feel protected from the police. Understanding police-related fear is important because it may impact civilians’ health, daily lives, and policy attitudes. To examine the prevalence, sources, and consequences of both personal and altruistic fear of the police, we surveyed a nationwide sample (N = 1,150), which included comparable numbers of Black (N = 517) and White (N = 492) respondents. Most White respondents felt safe, but most Black respondents lived in fear of the police killing them and hurting their family members. Approximately half of Black respondents preferred to be robbed or burglarized than to have unprovoked contact with officers. The racial divide in fear was mediated by past experiences with police mistreatment. In turn, fear mediated the effects of race and past mistreatment on support for defunding the police and intentions to have “the talk” with family youths about the need to distrust and avoid officers. The deep American racial divide in police-related fear represents a racially disparate health crisis and a primary obstacle to law enforcement's capacity to serve all communities equitably.